Relationship of Knowledge and Attitudes of Fertile Ages Against Family Planning at Garuda Pekanbaru Public Health Center - Yulita, Emi (Journal of Global Research in Public Health, 2018)
Family planning program is one of effort to reach the prosperity by way giving marriage advise and estranged pregnancy, pregnancy observation, which done by giving drug, installation of appliance and operate action to prevent pregnancy. This Research target is to know the knowledge and attitude illustration of fertile age couple toward family planning program in Public Health Center of Garuda Pekanbaru. This Research Type is descriptive research, the amount the population in this research is Fertile Age Couple in the public Health Center of Garuda Pekanbaru is 14.210 people, and the sample in this research is amounting to 99 people, with the intake sampel technique used by accidental sampling. The research done from the date of 10 July until 8 August 2009 in Public Health Center of Garuda Pekanbaru. Data collecting in this research through spreading questionnaire, data processing with the univarian analysis. Chi-Square analysis results obtained p = 0,000 meaning p <0.05 it can be concluded that the existence of Knowledge Relations and Attitudes of EFA to Family Planning in Garuda Pekanbaru Health Center. Untuk it is expected to health workers to maintain and further increase counseling health about family planning